Copper indium diselenide nanocrystalline silicon thin film solar cell with graphene as conductive material and preparation method thereof - DELIANG WU; CHUNLONG LI; YUNRONG LUO; DONGNI CHEN (2015)
The invention discloses a copper indium diselenide nanocrystalline silicon thin film solar cell with graphene as a conductive material and a preparation method thereof. P-type heavily doped graphene is used as a substrate; a p-type copper indium diselenide thin film is prepared on the p-type heavily doped graphene through an ion beam sputtering method; an n-type cadmium sulfide thin film is deposited on the surface of the p-type copper indium diselenide thin film through an evaporation method; an intrinsic graphene transition layer is prepared on the surface of the n-type cadmium sulfide thin film by using a chemical vapor deposition method; p-type and n-type nanocrystalline silicon thin films are prepared on the intrinsic graphene transition layer in sequence through a plasma enhanced chemical vapor deposition method; next an n-type heavily doped graphene thin film is prepared on the n-type nanocrystalline silicon thin film through the chemical vapor deposition method; finally metal electrodes are prepared on the surfaces of the n-type heavily doped graphene thin film and the p-type heavily doped graphene substrate through the evaporation method. The solar cell and the preparation method have the advantages that the manufacturing process is simple, the cost is low, the light wave absorption range of the conventional copper indium diselenide nanocrystalline silicon thin film solar cell is expanded, the advantages of high conductivity, high transmittance and good illumination thermal stability of the graphene are brought into full play, the conversion efficiency of the solar cell is improved, and the service life of the solar cell is prolonged.